Peran Kepala Desa Dalam Pembangunan Infrastruktur: Studi Kasus Desa Simpang Padang Kecamatan Bathin Solapan Kabupaten Bengkalis - Wardana, Geri; Zainal, Zainal (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2026)
This study aims to examine the role of the Village Head in the planning, implementation and supervision of infrastructure development in Simpang Padang Village, Bathin Solapan Sub-district, Bengkalis District. The study employs a qualitative descriptive approach, with data collected through structured interviews, direct observation and documentation. The research informants comprised the Village Head, the Village Secretary, the Head of Development Affairs, the Hamlet Heads, and the Village Facilitator. The research findings indicate that the Village Head plays an active role in coordinating village officials and the community, ensuring a participatory decision-making process, overcoming development obstacles through public awareness campaigns and consensus-building deliberations, and conducting direct supervision of project implementation in the field. Infrastructure development has a positive impact on community welfare, particularly in terms of improving the quality of roads and public facilities. However, development is still being carried out in stages due to budgetary constraints and local conditions. This study emphasises the importance of participatory governance, effective coordination, and adaptive leadership in supporting the success of rural infrastructure development.